Gravity Anomalies and Implications for Shallow Mantle Processes of the Western Cocos‐Nazca Spreading Center. Issue 5 (2nd March 2023) - Zheng, Tingting; Lin, Jian; Schouten, Hans; Smith, Deborah K.; Klein, Emily; Parnell‐Turner, Ross
Abstract: This study analyzes up‐to‐date gravity data in the Galapagos triple junction region to understand crustal structure and melt distribution beneath the propagating Cocos‐Nazca spreading center (CNSC). Application of a standard thermal model to the mantle Bouguer gravity anomaly (MBA) does not appear to result in a realistic crustal thickness in this region. The cross‐CNSC MBA profiles flatten and axial values increase from east toward the western end of the CNSC. A simple smoothing filter applied to the standard thermal model with different filter widths can explain the progressive flattening of the MBA and is interpreted as different distribution widths (concentrations) of partial melt in the mantle. The east‐west residual MBA gradient along the CNSC is similar to the east flank of the East Pacific Rise (EPR), suggesting that the along‐CNSC gradient could partly reflect the shallow mantle properties associated with the EPR. Plain Language Summary: This study investigates changes in crustal thickness and shallow mantle properties beneath the westward propagating Cocos‐Nazca spreading center (CNSC) by analyzing shipboard gravity data combined with satellite gravity data in the Galapagos triple junction region. By assuming a general 1‐D plate cooling model, we correct the age‐induced thermal effect of the lithosphere with a standard thermal model, which suggest thinner crust near the western tip of the CNSC increasing in thickness toward the east. However, results also indicate that the crust continues to thicken from the CNSC axis to the north and south edges of the gore, which does not seem realistic. Instead, these gravity signals most likely reflect properties within the shallow mantle, specifically a eastward decrease in the width (and hence increase in concentration) of melt within the shallow mantle beneath the CNSC. The residual gravity gradient along the CNSC axis is similar to that on the east flank of the East Pacific Rise (EPR), suggesting that the CNSC axis gravity gradient could in part reflect variation in the mantle density beneath the EPR. Key Points: Shipboard and satellite gravity data were used to explore the crustal structure in the Galapagos triple junction region The gravity‐derived crustal thickness with a standard thermal model does not appear to be realistic in this region A simple smoothing filter applied to the standard thermal model could explain gravity variation along the Cocos‐Nazca spreading center